1. ## Basic problem.

$\displaystyle A = \pi \cdot \left(\frac{x}{2\pi}\right)^2 = \frac{x^2}{4\pi}$

Can someone tell me the steps for this? I don't get how pi(x/2pi)^2 = x^2/4pi

2. Originally Posted by kmjt
$\displaystyle A = \pi \cdot \left(\frac{x}{2\pi}\right)^2 = \frac{x^2}{4\pi}$

Can someone tell me the steps for this? I don't get how pi(x/2pi)^2 = x^2/4pi
I believe this is the way to think about problem, but truthfully am not 100% sure -- Check it out. . . .

1. pi = pi/1

2. (x/2pi)^2 = (x^2)(pi)/(4pi^2)

3. pi x (x^2) = (x^2)pi/4pi^2) = x^2/4pi

3. Anyone else?

4. ## Ignore Previous Post

Pretty sure I am wrong. What I entered came out all wrong. Am new member. Must learn how to use MathType to make things clear!

5. Not a problem thanks for trying I have simplfied it myself and got it right.

6. Originally Posted by kmjt
$\displaystyle A = \pi \cdot \left(\frac{x}{2\pi}\right)^2 = \frac{x^2}{4\pi}$

Can someone tell me the steps for this? I don't get how pi(x/2pi)^2 = x^2/4pi
kmjt --

I was too tired and in too big of a hurry last night when I replied to your question. Sorry.

I should have just said to do the squaring of the terms in parenthesis, and then divide through by pi --

(x divided by 2pi) squared = x squared divided by 4pi squared. Dividing then by pi results in x squared divided by 4pi.